2001
DOI: 10.4314/wsa.v27i3.4980
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pulping effluents by using alum and clay - colour removal and sludge characteristics

Abstract: The effect of clay addition during alum coagulation, on the removal of colour from pulp-and-paper industry wastewaters, was investigated. Four types of clay, namely beige-and brown-sepiolites, calcium-and sodium-bentonites of different mesh sizes were used. Different quantities of alum and clay were applied, either singly or in combination, to the effluents of the wood-based pulpand-paper mill. Colour of the treated wastewater, the sludge volume index (SVI) and sludge cake resistance (SCR) of the sludge produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…However, the energy requirement and the use of high pressure reactors and associated equipment make the wet air oxidation of large volume of wastewater uneconomical. Chemical precipitation (and/or coagulation) using alum, ferric chloride, lime, ferrous sulphate and poly aluminium chloride (PAC) have been studied extensively [10][11][12][13][14]. Although economical, in comparison to other methods, the precipitation method has other associated drawbacks like dewatering and disposal of the generated sludge.…”
mentioning
confidence: 99%
“…However, the energy requirement and the use of high pressure reactors and associated equipment make the wet air oxidation of large volume of wastewater uneconomical. Chemical precipitation (and/or coagulation) using alum, ferric chloride, lime, ferrous sulphate and poly aluminium chloride (PAC) have been studied extensively [10][11][12][13][14]. Although economical, in comparison to other methods, the precipitation method has other associated drawbacks like dewatering and disposal of the generated sludge.…”
mentioning
confidence: 99%
“…Studies conducted in 2010 revealed that this wastewater is a continuous source of threat for receiving water body, the Kabul River. It also contaminates the drinking water quality of the nearby areas [11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…It includes salts of strong acids and weak basis such as Alum, ferric chloride, ferrous sulphate etc. as effective coagulants [14]. The advantage of coagulation treatment is the reduction of wastewater pollutants up to lowest level making it cost effective for secondary treatment [15].…”
Section: Introductionmentioning
confidence: 99%
“…The effluent generated is characterised by dark colour, foul odor and high organic content and extreme quantities of chemical oxygen demand (COD), biochemical oxygen demand (BOD) and pH (Pokhrel et al, 2004). The dark colour in paper mill effluent is caused due to the presence of organic ligands such as wood extractives, resins, products (Deilek et al, 2001). Industrialization has become an important factor to the development of a country's economy, through the establishment of plants and factories However, the waste or by-products discharged from them are severely disastrous to the environment consists various kind of contaminant which contaminate the surface water, ground water and soil Kumar and Thakur, 2017 3-(29.85%), TKN (25.83%), Na (26.94%), K (30.54%) and total hardness (21.56%) in the paper mill effluent were recovered after phyto-adsorption treatment using leaf powder of E. crassipes.…”
Section: Introductionmentioning
confidence: 99%